Characterization of vertical aligned carbon nanotube based devices - Poh, Priscilla Joo Yee (2019)
Vertical Aligned Carbon Nanotube (VACNT) has been proposed in the development of various types of sensors for its good mechanical and electrical properties. The advancement in the fabrication technique of VACNT has led to various successful development of flexible sensors. However, there is a lack of standard characterization system to test and record the results of the VACNT based sensors. This project aims to achieve computer vision for VACNT based devices and build a proper data acquisition program for the testing of the device samples. LabVIEW will be used to develop a customized data acquisition program with the use of a data acquisition unit and a source meter. The different addressing methods for the integration of the source meter available in LabVIEW is explored. The development of the program as well as the pros and cons of each addressing method are discussed in this report.